Control of phosphatidylserine biosynthesis through phosphatidylserine-mediated inhibition of phosphatidylserine synthase I in Chinese hamster ovary cells - Kuge, Osamu (The National Academy of Sciences, 1998)
Phosphatidylserine (PtdSer) synthesis in Chinese hamster ovary (CHO) cells occurs through the exchange of l-serine with the base moiety of phosphatidylcholine or phosphatidylethanolamine. The synthesis is depressed on the addition of PtdSer to the culture medium. A CHO cell mutant named mutant 29, whose PtdSer biosynthesis is highly resistant to this depression by exogenous PtdSer, has been isolated from CHO-K1 cells. In the present study, the PtdSer-resistant PtdSer biosynthesis in the mutant was traced to a point mutation in the PtdSer synthase I gene, pssA, resulting in the replacement of Arg-95 of the synthase by lysine. Introduction of the mutant pssA cDNA, but not the wild-type pssA cDNA, into CHO-K1 cells induced the PtdSer-resistant PtdSer biosynthesis. In a cell-free system, the serine base-exchange activity of the wild-type pssA-transfected cells was inhibited by PtdSer, but that of the mutant pssA-transfected cells was resistant to the inhibition. Like the mutant 29 cells, the mutant pssA-transfected cells grown without exogenous PtdSer exhibited an ≈2-fold increase in the cellular PtdSer level compared with that in CHO-K1 cells, although the wild-type pssA-transfected cells did not exhibit such a significant increase. These results indicated that the inhibition of PtdSer synthase I by PtdSer is essential for the maintenance of a normal PtdSer level in CHO-K1 cells and that Arg-95 of the synthase is a crucial residue for the inhibition.